2022
DOI: 10.1021/acs.joc.2c00477
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Catalyzed Radical Trifluoromethyl-Alkenylation of Alkenes or Alkynes with 2-Amino-1,4-naphthoquinones

Abstract: The first Fe-catalyzed three-component radical trifluoromethyl-alkenylation of alkenes with 2-amino-1,4-naphthoquinones and CF3SO2Na is reported. The developed reaction enables the highly regioselective preparation of a variety of valuable CF3-substituted 1,4-naphthoquinones in acceptable yields. In the light of the catalytic system, alkynes smoothly afford the corresponding three- or four-component trifluoromethyl-alkenylation products. This protocol features use of easily available and inexpensive reagents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Furthermore, the employment of the same 1,4‐naphthoquinone substrates in trifluoromethyl‐alkenylation reaction was reported recently by Tang [31] and co‐workers. In this procedure, Langlois’ reagent was applied as the CF 3 source, FeSO 4 ⋅7H 2 O as the catalyst, and K 2 S 2 O 8 as the oxidant providing the corresponding products in moderate to good yields (Scheme 20b).…”
Section: Alkenyltrifluoromethylation Reactionsmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, the employment of the same 1,4‐naphthoquinone substrates in trifluoromethyl‐alkenylation reaction was reported recently by Tang [31] and co‐workers. In this procedure, Langlois’ reagent was applied as the CF 3 source, FeSO 4 ⋅7H 2 O as the catalyst, and K 2 S 2 O 8 as the oxidant providing the corresponding products in moderate to good yields (Scheme 20b).…”
Section: Alkenyltrifluoromethylation Reactionsmentioning
confidence: 58%
“…In contrast, there is only a single publication in the literature regarding the functionalization of the carbon‐carbon triple bond. Very recently, Tang [31] et al. reported the iron‐catalyzed radical trifluomethyl‐alkenylation reaction of alkenes with 2‐amino‐1,4‐naphtoquinones using Langlois’ reagent, described above.…”
Section: Alkenyltrifluoromethylation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been displayed as high regioselectivity and functional group tolerance. 14 Behera and co-workers developed an efficient and scalable protocol for the synthesis of trifluoromethylated chromones from readily accessible o-hydroxyphenyl enaminones. The transformation is affected by the Langolis reagent in DMSO with a catalytic amount of Cu(OAc)2, and TBHP oxidant at room temperature.…”
Section: Synopen Spotlightmentioning
confidence: 99%
“…7 Tang et al reported three-component trifluoromethyl alkylation and alkenylation reactions with 2-aminonaphthoquinones by using alkenes and alkynes as intermediary radical acceptors. 8…”
Section: Introductionmentioning
confidence: 99%